The Reflection of Edmund Burke’s Sublime in Samuel Taylor Coleridge’s Selected Poetry - Aziz ur Rehman; Sania Gul; Lubna Ayaz (University of Chitral Journal of Linguistics and Literature)
This paper explores Edmund Burke’s concept ‘the sublime’ in Samuel Taylor Coleridge’s poetry. Coupled with his concept of ‘the beautiful’, Burke’s the sublime features conspicuous in creative arts. While beauty is an integral constituent or rather product of art, the sublime is no less desirable in amplifying a given piece of art. Unlike the beautiful, reflection of the sublime is considerably rare in poetry specifically the romantic. Coleridge is an exception in creating sublime effect in his poetry. His major poems especially The Rime of the Ancient Mariner and Kubla Khan not only reflect but almost embody the sublime as shown in this analysis. The secret of Coleridge’s fame as a supernatural poet owes largely to his use of the sublime. While the thematic critiques of Coleridge’s poetry are overshadowed by the supernatural, this brief textual analysis is an improvement in being different, entailing the sublime.